Morphological and behavioral determinants of individual trophic niche variation in anurans - Diaz-Perez, Jorge Arnaldo [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Determining whether co-occurring organisms differ in their ecological niches, particularly in their trophic resource use, and what causes these differences has long been a central question in ecology. In recent years, the study of these topics using an individual-based approach has increased substantially and constitutes the focus of this thesis. The proximate causes of individual trophic niche variation may be morphological, behavioral, or physiological, or may arise from interactions among these factors. Despite advances in understanding these causes, the role of morphology as a prevalent factor driving individual niche variation across populations remains unclear, and studies often do not consider prey traits or apply an explicit functional mechanistic approach linking consumer morphology to trophic niche variation. In addition, the limited number of ecological systems studied and the historical disconnection between individual-based approaches to study ecological niche variation (i.e., individual specialization) and behavior (i.e., animal personality) have constrained the understanding of the behavioral causes of trophic niche variation within populations. To contribute to filling these knowledge gaps, this thesis integrates three chapters addressing the role of morphology (first chapter) and exploratory behavior (second and third chapters) in individual trophic niche variation, using anurans as a model system. Individual trophic niches were quantified using gut content and stable isotope analyses; feeding morphology (i.e., individual head shape) was characterized using geometric morphometrics; and individual exploratory levels were estimated through behavioral experimental assays. The main results of this thesis reveal that (i) morphology is an underlying cause of individual variation in consumed prey traits (size and mobility), and individual trophic niche specialization can be promoted by an increased strength of the relationship between morphology and diet; (ii) consistent individual differences in exploratory behavior drive variation in individual dietary niches but depending on sex and body size, and higher levels of exploration promote greater temporal variation in individual trophic niches; and (iii) predator proactivity in exploration-related behaviors drives interindividual differences in the mobility of consumed prey, with contrasting patterns between sexes. Together, these findings highlight the underappreciated role of morphology and the joint role of behavior and intrinsic factors (i.e., body size and sex) in shaping individual diets, contributing to the understanding of the proximate causes of trophic niche variation within natural populations.

Determinar se organismos que coexistem diferem em seus nichos ecológicos, particularmente no uso de recursos tróficos, e quais são as causas dessas diferenças tem sido, há muito tempo, uma questão central na ecologia. Nos últimos anos, o estudo desses temas por meio de uma abordagem baseada no indivíduo aumentou substancialmente e constitui o foco desta tese. As causas proximais da variação individual no nicho trófico podem ser morfológicas, comportamentais ou fisiológicas, ou podem surgir de interações entre esses fatores. Apesar dos avanços na compreensão dessas causas, o papel da morfologia como um fator prevalente que determina a variação individual do nicho nas populações permanece incerto, e os estudos frequentemente não consideram as características das presas nem implementam uma abordagem funcional mecanicista explícita que vincule a morfologia do consumidor à variação do nicho trófico. Além disso, o número limitado de sistemas ecológicos estudados e a desconexão histórica entre abordagens baseadas no indivíduo para o estudo da variação do nicho ecológico (i.e., especialização individual) e do comportamento (i.e., personalidade animal) têm restringido a compreensão das causas comportamentais da variação do nicho trófico dentro das populações. Para contribuir para o preenchimento dessas lacunas de conhecimento, esta tese integra três capítulos que abordam o papel da morfologia (primeiro capítulo) e do comportamento exploratório (segundo e terceiro capítulos) na variação individual do nicho trófico, utilizando anuros como sistema modelo. O nicho trófico dos indivíduos foi quantificado por meio de análises de conteúdo estomacal e de isótopos estáveis; a morfologia alimentar (i.e., o formato da cabeça dos indivíduos) foi caracterizada utilizando morfometria geométrica; e os níveis individuais de exploração foram estimados por meio de ensaios comportamentais experimentais. Os principais resultados desta tese revelam que (i) a morfologia é uma causa subjacente da variação individual nas características das presas consumidas (tamanho e mobilidade), e que a especialização individual do nicho trófico pode ser promovida por um aumento na força da relação entre morfologia e dieta; (ii) diferenças individuais consistentes no comportamento exploratório determinam a variação nos nichos alimentares individuais, mas de maneira dependente do sexo e do tamanho corporal, e níveis mais elevados de exploração promovem maior variação temporal nos nichos tróficos individuais; e (iii) a proatividade do predador em comportamentos relacionados à exploração determina diferenças interindividuais na mobilidade das presas consumidas, com padrões contrastantes entre os sexos. Em conjunto, esses achados destacam o papel subestimado da morfologia e o papel conjunto do comportamento e de fatores intrínsecos (i.e., tamanho corporal e sexo) na determinação das dietas individuais, contribuindo para a compreensão das causas proximais da variação do nicho trófico em populações naturais.
Determinantes morfológicos e comportamentais da variação individual do nicho trófico em anuros
Keywords: Niche variation; Animal personality; Functional morphology; Trophic niche; Geometric morphometrics; Individual specialization; Amphibians; Stable isotopes; Nicho (Ecologia); Especialização individual; Nicho trófico; Personalidade animal; Morfologia (Animais); Morfometria geométrica; Isótopos estáveis; Anuros